Single-nuclei RNA sequencing uncovers heterogenous transcriptional signatures in Parkinson’s disease associated with nuclear receptor-related factor 1 defect - Piniel Alphayo Kambey; Wen-Ya Liu; Jiao Wu; Bakwatanisa Bosco; Iqra Nadeem; Kouminin Kanwore; Dian-Shuai Gao (Neural Regeneration Research, 2023)
Previous studies have found that deficiency in nuclear receptor-related factor 1 (Nurr1), which participates in the development, differentiation, survival, and degeneration of dopaminergic neurons, is associated with Parkinson’s disease, but the mechanism of action is perplexing. Here, we first ascertained the repercussion of knocking down Nurr1 by performing liquid chromatography coupled with tandem mass spectrometry. We found that 231 genes were highly expressed in dopaminergic neurons with Nurr1 deficiency, 14 of which were linked to the Parkinson’s disease pathway based on Kyoto Encyclopedia of Genes and Genomes analysis. To better understand how Nurr1 deficiency autonomously invokes the decline of dopaminergic neurons and elicits Parkinson’s disease symptoms, we performed single-nuclei RNA sequencing in a Nurr1 LV-shRNA mouse model. The results revealed cellular heterogeneity in the substantia nigra and a number of activated genes, the preponderance of which encode components of the major histocompatibility II complex. Cd74, H2-Ab1, H2-Aa, H2-Eb1, Lyz2, Mrc1, Slc6a3, Slc47a1, Ms4a4b, and Ptprc2 were the top 10 differentially expressed genes. Immunofluorescence staining showed that, after Nurr1 knockdown, the number of CD74-immunoreactive cells in mouse brain tissue was markedly increased. In addition, Cd74 expression was increased in a mouse model of Parkinson’s disease induced by treatment with 6-hydroxydopamine. Taken together, our results suggest that Nurr1 deficiency results in an increase in Cd74 expression, thereby leading to the destruction of dopaminergic neurons. These findings provide a potential therapeutic target for the treatment of Parkinson’s disease.